Microbiome compositional changes and clonal engraftment in a phase 3 trial of fecal microbiota, live-jslm for recurrent Clostridioides difficile infection - Josh Claypool; Gustav Lindved; Pernille Neve Myers; Tonya Ward; Henrik Bjørn Nielsen; Ken F. Blount (Gut Microbes)
Live microbiota therapies have shown promise in many gastrointestinal diseases, including in the prevention of recurrent Clostridioides difficile infections (rCDI); however, frameworks for their pharmacokinetic and pharmacodynamic analysis are not fully established. Fecal microbiota, live-jslm (RBL) is the first microbiota-based product approved by the US Food and Drug Administration for the prevention of rCDI and was superior to placebo in the PUNCH™ CD3 phase 3 clinical trial (NCT03244644). In this analysis, deep shotgun metagenomic sequencing was used to assess changes in gut microbiome compositions of participants and engraftment of bacterial clonal populations (i.e. strains) from RBL to recipients. Among RBL responders, gut microbiota shifted toward compositions that resembled healthy donors as early as 1 week after RBL administration; the resulting microbiota compositions included clonal populations that engrafted from RBL to recipients. Engraftment was higher in RBL responders compared with non-responders, and many clonally engrafted populations persisted for ≥ 6 months. Bacteroidia species were among the most effectively engrafted species from RBL. This study utilizes data from a large clinical trial to establish a method with high specificity for exploring clonal engraftment from microbiota-based treatments to facilitate future pharmacokinetic and pharmacodynamic analyses.Clinicaltrials Registration: NCT03244644